Tourism, Its Aspects and Enhancing Tourism in Nepal through Bay of Bengal Forum - Paudel, Damaru Ballabha (Humanities and Social Sciences Journal, 2023)
Tourism is an emerging sector of Nepali economy that generates foreign exchange earnings and adds to the country's balance of payments. Nepal is a member of the Bay of Bengal Initiative for Multi-sectoral Technical and Economic Cooperation (BIMSTEC) since 2004. Nepal and BIMSTEC member states have historical, geographic, physical, cultural, economic/financial, environmental/natural, people to people, technological, professional and media (social or print) linkages. As BIMSTEC bridges South Asia to South East Asia, Nepal has enormous potentials of economic growth through tourism earning using BIMSTEC Mechanism. By branding of BIMSTEC tourism circuits and marketing tour packages in Europe, America, China, and other top tourist sending countries, both BIMSTEC region and Nepal can gain foreign exchange from tourism which can help them to prosper together.